Pengaturan Hak Jual Beli Tanah Adat oleh Desa Adat di Bali sebagai Subjek Hukum - Putu Ardi Kumara; Komang Satria Wibawa Putra; I Nyoman Budiana; Putu Eva Ditayani Antari (Lembaga Pengembangan Kinerja Dosen, 2025)
The recognition of Traditional Villages as legal subjects in the national legal system as regulated in Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia, Law Number 5 of 1960 concerning Basic Agrarian Principles Regulations, and Bali Province Regional Regulation Number 4 of 2019 concerning Traditional Villages in Bali has consequences for the regulation of ownership rights and control of customary land in Bali. This regulation still does not provide clarity regarding the scope of authority of Traditional Villages in carrying out land buying and selling transactions, giving rise to unclear norms and implications for legal uncertainty. This research aims to analyze the regulation of ownership rights and land control by Traditional Villages in Bali and examine the position of Traditional Villages as legal subjects in the national land law system. This research is normative legal research with a statutory approach, conceptual approach and historical approach. Legal materials are analyzed qualitatively using descriptive analytical methods. The results of the research show that the recognition of Traditional Villages as legal subjects has obtained constitutional and normative legitimacy, however, regulations regarding land ownership and control rights are not yet harmonious, so they still give rise to differences in interpretation in practice. There is a need for harmonization of land regulations to create legal certainty, provide protection for the rights of customary law communities, and support sustainable management of customary land.